2022
DOI: 10.3389/fpubh.2022.854343
|View full text |Cite|
|
Sign up to set email alerts
|

COVID-19 Preventive Measures in Northern California Jails: Perceived Deficiencies, Barriers, and Unintended Harms

Abstract: BackgroundCarceral facilities are high-risk settings for COVID-19 transmission. Little is known about the hidden burden of infection or practical barriers to infection control in these settings, especially in jails. There is also limited research on the mental health impacts of the pandemic among people living and working in carceral facilities.MethodsBetween July 8, 2020 and April 30, 2021, we performed SARS-CoV-2 rapid antibody testing and administered a questionnaire among residents and staff of four Northe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Five results examined the impact of de-densification on infection rates (Chin, Ryckman, et al, 2021; Jimenez et al, 2020; Leibowitz et al, 2021; Liu et al, 2022; Vest et al, 2021). Vest et al (Vest et al, 2021), Leibowitz et al (Leibowitz et al, 2021), and Jimenez et al (Jimenez et al, 2020) investigated links between how full a prison is and infection rates.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five results examined the impact of de-densification on infection rates (Chin, Ryckman, et al, 2021; Jimenez et al, 2020; Leibowitz et al, 2021; Liu et al, 2022; Vest et al, 2021). Vest et al (Vest et al, 2021), Leibowitz et al (Leibowitz et al, 2021), and Jimenez et al (Jimenez et al, 2020) investigated links between how full a prison is and infection rates.…”
Section: Resultsmentioning
confidence: 99%
“…All three studies concluded that decarceration may be an effective mitigation measure. Chin et al (Chin, Ryckman, et al, 2021), Leibowitz et al (Leibowitz et al, 2021), and Liu et al (Liu et al, 2022) demonstrated that having a smaller number of cellmates reduces the risk of COVID-19 infection for people who are detained in state prisons. Chin et al (Chin, Ryckman, et al, 2021) found that dormitory residents had higher infection rates than cell residents (adjusted hazard ratio, 2.51; 95% CI, 2.25-2.80).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations